The toll booths analogy / Muhammad Aiman Abdul Halim - Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2023)
This is an email I received recently from Touch 'n Go eWallet. Interesting to see the number of tolls I have passed in 2022. If it is up to me, I would never bother to keep track of it. Did I learn anything from all those toll passings? Perhaps, it is the "toll booths analogy". We could use the same approach we use when passing a toll booth in our everyday life. Try to visualise in your mind, you are driving on a highway and approaching a toll booth. There are cash lanes, Touch 'n Go lanes, Smart Tag lanes, as well as the RFID lanes. Many different ways to get through the toll. What do we do when we approach these tolls? Naturally, we will slow down. Then, we will look at the available booths and start to think about what we have at our disposal (for example, RFID). Then we will look for the shortest line, the one that can get us through the fastest. We can hope for the best, but sometimes things will not go our way. Problems could happen, for example, the car in front of us might cause delays and we end up passing the tolls slightly later than we expected. Such is life. Everybody has their own goals and destinations in life. We can always make the plans and efforts to move towards our goals. It is good if we can achieve those goals quickly, but the toll booths taught me that sometimes, it is good to slow down for a moment to analyse the situation. This could give us clarity and better perspectives to make better choices in life. We can hope for the best as we make our choices, but we must also be prepared for the worst. Things can go unexpectedly in life, and we need to learn to embrace these moments as well.